Investigating judge — new party to a proceeding in criminal justice of the Republic of Kazakhstan - Sultanbekova, G.B.; Abzalbekova, M.T. (KSU publ., 2015)
Article examines the issues of establishment and development of judicial control in the Republic of Kazakhstan, introduction of new party to a proceeding in criminal justice of Kazakhstan — investigating judge. There are issues, related to future expansion of powers of investigating judge, about place and role of judge, who executes the operative judicial control; issues are examined, related to legal nature of investigating judge. Here are also examined the issues on authorization of investigating judge for sanctioning of non-public investigatory actions.
Keywords: investigating judge; judge for introductory investigation; operative control of pre-trial procedure; optimization of pre-trial procedure in criminal justice of the Republic of Kazakhstan; legal status; judicial control of observance of rights; freedoms and interests of people in criminal justice